Implementasi Kebijakan Disiplin Pegawai Negeri Badan Kepegawaian Daerah Kota Bandung - Ika Widiastuti; Luluh Abdillah Kurniawan; Pandu Adi Cakranegara (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
Implementation of policies carried out by implementers, namely the implementation of civil servant discipline. One way to know the discipline of employees is by the presence of fingerprints. This aims to improve employee performance. But in its implementation there are violations committed by policy implementers (implementers) and target groups of civil servants BKD Bandung City. The purpose of the research is to understand the implementation of civil servant discipline in Bandung so that the performance of employees can be improved. The research method uses qualitative methods. The result of the research is the implementation of civil servant disciplinary policy in BKD Bandung city has not been able to run to the maximum because there is no written regulation from the leadership of BKD Bandung City, has not established a Team of Examiners / Supervisors of Disciplinary Punishment Considerations, has not implemented routine supervision conducted by implementers, sanctions can not be applied firmly by the violators.